Calcific Uremic Arteriolopathy on Multimodal Combination Therapy: Still Unmet Goal - Usman Hammawa Malabu; Valli Manickam; George Kan; Susan Lynette Doherty; Kunwarjit Singh Sangla (International Journal of Nephrology)
Background. Calcific uremic arteriolopathy (CUA) or calciphylaxis though generally noted for its high mortality, recent case reports have shown promising results using single agent therapies. However, it is not clear whether combination therapeutic agents will improve course of the disease. Objective. To determine clinical outcome in subjects with CUA on multimodal treatment. Methods. All patients with end-stage renal failure (ESRF) at The Townsville Hospital, Australia, from April 1, 2006, to March 31, 2011, with diagnosis of CUA were retrospectively studied. Results. Six subjects with CUA (4 females and 2 males) were on various combination therapeutic agents comprising sodium thiosulphate, hyperbaric oxygen, prednisolone, cinacalcet, and parathyroidectomy in addition to intensified haemodialysis, specialist local wound care, and antibiotics. The wounds failed to heal in 3 patients while 5 of the 6 subjects died; cause of death being sepsis in 3 and myocardial infarction in 2. Conclusion. Prognosis of CUA remains poor in spite of multimodal combination therapy. Further prospective studies on a larger population are needed to verify our findings.